(untitled) (International Educators Conference, 2025)
This article analyzes the pedagogical and philosophical views of the Jadid movement and highlights their role in the process of national awakening. Jadid reforms in the field of education, new method schools, ideas about personal development, and the philosophy of national awakening are separately studied. The services of Jadids in awakening the public consciousness through the national press, literature, and enlightenment are also highlighted. The article analyzes the importance of the Jadid heritage in the formation of the current education system and the national idea on a scientific basis.